Visuomotor skills in school children: A cross-cultural study Peru-Brazil - Velasco Valderas, Rosa (2017)
The principal aim of the study was evidences of the validity offered psicométrica of the Gestáltico Visomotor Bender’s Test (TGV) and the System of Qualification of Gradual Punctuation (B-SPG). In this respect the maturity was appraised visomotora at 108 children of both sexes by ages understood between 6 and 10 years of primary age of mixed colleges of level of Metropolitan Lima and to compare these results with an equal sample (108) of children of the condition of Sao Paulo State in Brazil. Thinking that Bender’s TGV with the B-SPG is a consistent test where all the articles contribute to the test. Significant differences being observed in function to the age where to major minor age number of mistakes and minor total score. This inversely proportional relation between the age and the number of mistakes was described as method to measure the maturity visomotora and was established by Bender in his original study in the year 1955. On the other hand, they did not find significant differences in function to the sex.